Dampak Fenomena Konten Anomali Brainrot terhadap Perkembangan Kognitif Anak Usia Dini: Studi Kasus di RA Al Ahmad Sidoarjo, Indonesia - Milla Ahmadia Apologia; Ali Masykuri; Tantri Risda Zubaidah (JCE (Journal of Childhood Education), 2025)
The rapid proliferation of short-video platforms on various social media networks has recently increased early childhood exposure to anomalous digital content, popularly referred to as 'brainrot anomalies.' This term does not constitute a medical diagnosis but serves as a social label for ultra-short, repetitive content featuring visual absurdities with limited educational value. This study aims to explore children's responses to anomalous content and its implications for attention span and cognitive development in early childhood. Employing a qualitative approach with a descriptive case study design, the research was conducted at RA Al-Ahmad, Indonesia, involving ten children aged 5–6 years. Data were collected through structured observations, semi-structured interviews with parents, and documentation, followed by an analysis consisting of (a) data reduction, (b) data display, and (c) conclusion drawing. Data validity was ensured through method and source triangulation techniques. The findings indicate that 52% of the subjects exhibited a high level of interest, characterized by intense focus and repetitive imitative behavior toward anomalous video content, which potentially influences the child's perception of concrete reality. Furthermore, 30% of the subjects showed moderate interest and were easily diverted to other activities, while 18% displayed low interest. Although no direct evidence of cognitive decline was found, dominant exposure to rapid and repetitive content tends to reduce opportunities for deeper cognitive stimulation. In conclusion, while anomalous short-video content does not directly cause cognitive impairment, it is associated with shifts in attention patterns among young children. Practically, this study recommends active mediation by parents and educators, the selection of developmentally appropriate content, and the regulation of screen time duration.